Template induced structural isomerism and enhancement of porosity in manganese(II) based metal-organic frameworks (Mn-MOFs) - Panda, Tamas; Pachfule, Pradip; Banerjee, Rahul (Chemical Communications, 2011)
Three new metal-organic framework isomers have been synthesized by using the organic linker 5-triazole isophthalic acid and Mn(NO3)(2)center dot xH(2)O. Structural conversions from non-porous to porous MOFs due to the template effect have been observed. The cross-sectional pore apertures of the resulting Mn-MOFs are comparable to the molecular dimensions of the template (pyrazine and 4,40-bipyridine). The periodic increased porosity in Mn-MOFs depending on the size of the template used has been further confirmed by the CO2 adsorption isotherms.